Characterization of a novel AEL allele harboring a c.28 + 5G>A mutation on the ABO*A2.01 background: a study utilizing PacBio third-generation sequencing and functional assays - Shao, Lin-Nan; Song, Wen-Qian; Zhou, Lu; Pan, Ling-Zi; Duan, Ying; Xiao, Nan; Zhou, Shi-Hang; Liang, Xiao-Hua (Frontiers in Immunology, 2024)
BackgroundMutations in the ABO gene, including base insertions, deletions, substitutions, and splicing errors, can result in blood group subgroups associated with the quantity and quality of blood group antigens. Here, we employed third-generation PacBio sequencing to uncover a novel AEL allele arising from an intron splice site mutation, which altered the expected A2 phenotype to manifest as an Ael phenotype. The study aimed to characterize the molecular mechanism underlying this phenotypic switchMethodsA 53-year-old healthy male blood donor with an atypical agglutination pattern was investigated. PacBio sequencing was used to sequence the entire ABO gene of the proband. In silico analysis predicted aberrant splicing, which was experimentally verified using a minigene splicing assay.ResultsBased on serological characteristics, the proband was determined to have an Ael phenotype. Sequencing revealed heterozygosity for ABO*O.01.02 and a novel ABO*A2.01-like allele with an additional c.28 + 5G>A mutation in intron 1. In silico predictions also indicated that this mutation is likely to cause aberrant splicing. Minigene analysis suggested that this mutation disrupted the 5’-end canonical donor splice site in intron 1, activated a cryptic donor site, and resulted in a 167 bp insertion, producing a truncated glycosyltransferase (p.Lys11Glufs*66). Meanwhile, a small amount of the wild type transcript was also generated through normal splicing, contributing to the Ael phenotype.ConclusionA novel AEL allele was identified in a Chinese male blood donor on the ABO*A2.01 background, characterized by the c.28 + 5G>A variant. This study provides insights into the molecular basis of blood group antigen variation.